Expression of AgNOR in Benign, Borderline and Malignant Epithelial Tumors of Ovary and Its Correlation with Tumor Grading (Journal of Enam Medical College, 2024)
Background: Surface epithelial tumor is the most common type of ovarian tumor making up 65% of all ovarian neoplasms. The proliferative activity of tumor can be estimated by many methods and the analysis of silver binding nucleolar organizer region (AgNOR) is one of them. Two types of AgNOR counts were calculated – mAgNOR and pAgNOR. Objective: To find out expression of AgNOR staining in benign, borderline and malignant epithelial tumors of ovary and its correlation with tumor grading. Materials and Methods: This cross-sectional study was conducted in the department of Pathology, Sir Salimullah Medical College, Dhaka from March 2018 to July 2020. In this study 70 diagnosed cases of benign, borderline and malignant epithelial tumors of ovary were enrolled. Corresponding paraffin blocks were collected. Ethical practice was ensured in every step of the study. Statistical analysis was carried out as required. Statistical significance was considered at